2017
DOI: 10.1073/pnas.1614055114
|View full text |Cite
|
Sign up to set email alerts
|

How electron two-stream instability drives cyclic Langmuir collapse and continuous coherent emission

Abstract: Continuous plasma coherent emission is maintained by repetitive Langmuir collapse driven by the nonlinear evolution of a strong electron two-stream instability. The Langmuir waves are modulated by solitary waves in the linear stage and electrostatic whistler waves in the nonlinear stage. Modulational instability leads to Langmuir collapse and electron heating that fills in cavitons. The high pressure is released via excitation of a shortwavelength ion acoustic mode that is damped by electrons and reexcites sma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 31 publications
2
22
0
Order By: Relevance
“…It is analogous to Landau damping absorption of plasmons during collapse of Langmuir turbulence. 17,18 In the latter case, plasmon Landau damping arrests collapse, leaving an "empty cavity," without its "filling" of Langmuir wave pressure. Table I compares these two processes.…”
Section: Introductionmentioning
confidence: 99%
“…It is analogous to Landau damping absorption of plasmons during collapse of Langmuir turbulence. 17,18 In the latter case, plasmon Landau damping arrests collapse, leaving an "empty cavity," without its "filling" of Langmuir wave pressure. Table I compares these two processes.…”
Section: Introductionmentioning
confidence: 99%
“…Observations and laboratory experiments have discovered the Hall field and Hall current associated with fast collisionless magnetic reconnection 10,12 , but no direct experimental or observational evidence has been found to show that the rate is irrelevant to the dissipation mechanism [22][23][24][25] . On the other hand, observations of solar flares found that magnetic reconnection may commonly be turbulent as evidenced by the filamentary structure of magnetic field, non-thermal heating observed in X-ray, and coherent radio emissions that are likely results of electron two-stream instability [26][27][28] . The reconnection rate in solar flares estimated by the variability of magnetic flux around magnetic null-points varies in a wide range, from the moderate 0.1 V A to very fast 0.5-0.6 V A 29 -much higher than the maximum Hall-reconnection rate from simulations.…”
Section: Introductionmentioning
confidence: 99%
“…Simulations show that the most unstable k of the instability changes as the plasma evolves, which can be confirmed by simultaneously collecting the scattered light from multiple angles. One can simultaneously measure the time evolution of the electron and ion features at several ks, which will enable the hierarchy of kinetic instabilities to be established (41,42) and track the evolution of the plasma from a quiescent to turbulent state (15).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms and time scale by which plasma electrons evolve from an anisotropic to a thermal state are important but unsolved experimental problems in basic plasma science. The kinetic plasma instabilities due to anisotropic plasmas are thought to occur in recombination x-ray lasers based on OFI plasmas (7), gamma ray flashes (8) and bursts (9), electron-positron plasmas (10), collisionless shocks (11), growth and filamentation of magnetic fields in plasmas (12), electron cloud effects in storage rings (13) and proton synchrotrons (14), solar corona and interplanetary medium (15), solar wind trapped in the ionosphere by Earth's magnetic field (16,17), neutrino-plasma interactions that may occur in supernova explosions (18), quark-gluon plasmas produced in heavy-ion beam collisions (19,20), and hot-electron transport in fast ignition-inertial confinement fusion (21,22). Given the extremely broad range of situations that give rise to kinetic instabilities, a voluminous theoretical body of work exists on the kinetic theory of plasmas.…”
Section: Introductionmentioning
confidence: 99%